(untitled) (Journal of Hama University, 2024)
The research was carried out twice in a row in the years 2022-2023 at the Stemerkho facility for the production of agricultural mushrooms Agaricus bisporus, and included five treatments: 1- Control (without additives), 2- Adding biochar, concentration of 4 g/l, 3- Adding selenium, concentration of 10-5 g/L, 4- Adding honey, concentration of 15 ml/L, 5- Adding sodium nitrate, concentration of 4 g/L, to the malt agar medium, with the aim of studying its effect on the growth of the gametophyte of the mother culture (G0).). The results of the average of the two experiments showed that all treatments of adding compounds were significantly superior to the control in all the studied characteristics. The treatment of adding sodium nitrate, concentration of 4 g/l, was significantly superior to the rest of the treatments in the fungal colony diameter(79.6)mm and in the terms of the time required for the completion of mycelium growth (18) days, growth speed (4.42) mm/day, and growth coefficient (30.95) mm2/day, compared to the period of completion of growth in the control (25) days, growth speed (2.09) mm/day, and growth factor (14.64) mm2/day. In terms of the beginning date of mycelium growth, the sodium nitrate and selenium treatments were superior to the rest of the treatments.